A Study on Tourism Services with special reference to Medical Tourism of Tamil Nadu - Raju, Srinivasan (IJRDO - Journal of Business Management, 2018)
Medical Tourism is a growing potential for India’s health care products and medical tourism of late in domestic as well as inbound tourist market. Medical tourism is a blend of tourism and health thereby known as ‘health or medical tourism.” It can be broadly defined as ‘a provision of ‘cost effective’ private medical care in collaboration with the tourism industry for patients needing surgical and other forms of specialized treatment. This paper addresses the concept of medical tourism in India and the government strategies for the development of tourism in India